A Hybrid Evaluation Approach for Designing Complex Urban Scenarios: Application for the T.I.T. Area (China). (10th June 2016) - Bottero, Marta; Armando, Alessandro; Bonino, Michele; Frassoldati, Francesca; Bruno, Edoardo; Federighi, Valeria
Abstract: This paper illustrates a long-term research that aims at proposing a multi-dimensional and multi-level integrated approach for supporting strategic planning and design in the domain of urban projects. The proposed framework is based on the combined use of different tools for designing complex urban transformation processes, following the subsequent phases for the definition of the projects, from very general transformation scenarios to a more detailed preliminary project. The multi-methodological approach is organized according to subsequent steps, including SWOT analysis, stakeholders analysis and Multicriteria Analysis, taking into account both the methodology of the Analytic Hierarchy Process and the Multi Attribute Value Theory. The evaluation is applied to a real-world decision problem related to the further on-going transformations in a former industrial area in Guangzhou (China) that has been recently regenerated as the T.I.T. Creative Zone.